Essays on corruption, allocative inefficiency, and mergers and acquisitions - Abudu, Derrick S. (2020)
The aim of this thesis is to unearth, for developing countries, how investment climate constraints – i.e., electricity supply and corruption – affect firms’ performances and the misallocation of production inputs (i.e., capital and labour); as well as the efficacy of tax incentives in attracting inward investments in the form of mergers and acquisitions (M&As). The first chapter assesses the implication of electricity shortages on the allocative efficiency (or misallocation) of capital and labour for a sample of 750 Ghanaian manufacturing firms spanning the period 2011–2015. The motivation for and relevance of this empirical inquest stems from insights from nascent literature (Restuccia and Rogerson 2008; Banerjee and Duflo 2005; Hsieh and Klenow 2009) that demonstrate how allocative inefficiency of production inputs contributes to the low aggregate total factor productivity (TFP) in developing countries. The study’s findings suggest that when faced with unreliable and insufficient power supply, firms respond by curtailing the employment of capital, labour, and compensation (wages) to the latter. Additionally, electricity shortages appear to inhibit firms’ efficiency (TFP) performance. What is more, electricity shortages are found to also increase the misallocation of or the allocative inefficiency of capital and labour. This effect is more pronounced for firms that own generators implying that for these set of firms, which are also those most likely more reliant on electricity, self-generation is not sufficient to attenuate the adverse effects of insufficient and unreliable power supply from the national grid. The last set of results indicate that, particularly for the misallocation of capital, this effect is more pronounced for firms that are electricity constrained. A finding which leads to the conclusion that these group of firms have capital or production techniques that are more electricity reliant. The second chapter investigates the impact of tax incentives on inward foreign investments in the form of mergers and acquisitions (M&As) for a sample of 91 developing countries. Although the extant literature (Hines, 1996; Devereux and Griffith, 1998; Bénassy-Quéré, Fontagné and Lahrèche-Révil, 2005; Huizinga and Voget, 2009) evidentially informs us about the sensitivity of firm location decision or FDI to taxation particularly for advanced countries, little is known about the efficacy of conditional (or targeted) tax incentives in inducing foreign investors, particularly for developing countries. This study uncovers that concessionary tax rates have the tendency to attract inward M&As into developing countries. This finding is found to be more pronounced for concessionary tax rates that are geared towards or conditional on investors locating in a specific location or SEZs or contributing to domestic exporting activities. Unimpressively, the quantitative magnitudes are rather modest in that, for instance, a developing country will have to reduce tax rates by as much as 1.6% in order to attract a single inward M&A. The last (third) chapter uses firm-level data from the World Bank’s Enterprise Surveys to examine the economic consequences of corruption on the performances of firms in Africa. The novelty of this chapter stems from the fact that most studies (Aidt 2009; P. G. Méon and Weill 2010; Méndez and Sepúlveda 2006; Mauro 1995) that have probed this issue have been macro-based hence failing to unearth any micro insights, and the only micro-based study (Fisman and Svensson 2007) was undertaken for a cross-section of Ugandan firms. The results suggest that firms that are likely to be more established – i.e., older and larger firms – are less likely to engage in bribery payment, rather it is the least productive ones that are more likely to do so. The chapter’s findings further reveal that corruption has both a contemporaneous and lag effect on firm performances in Africa. Finally, the results confirm that this negative effect is more pronounced for larger and older firms than small and medium-sized firms and young firms.